Пошаговое объяснение:
1)
10целых 5/8 - х = 7целых 3/5
х = 10целых 5/8 - 7целых 3/5
х = 10целых 25/40 - 7целых 24/40
х = 3целых 1/40
2)
(х - 2целых 7/8) + 3целых 5/6 = 4целых 2/3
х - 2целых 7/8 = 4целых 2/3 - 3целых 5/6
х - 2целых 7/8 = 4целых 4/6 - 3целых 5/6
х - 2целых 7/8 = 3целых 10/6 - 3целых 5/6
х - 2целых 7/8 = 5/6
х = 5/6 + 2целых 7/8
х = 20/24 + 2целых 21/24
х = 2целых 41/24
х = 3целых 17/24
3)
4/5 - ( х + 1/60 ) = 2/3
х - 1/60 = 4/5 - 2/3
х - 1/60 = 12/15 - 10/15
х - 1/60 = 2/15
х = 2/15 + 1/60
х = 8/60 + 1/60
х = 9/60
х = 3/20
1) - 6 1/3 + 4 2/3 = - 5 4/3 + 4 2/3 = - 1 2/3
2) - 7,6 - 12,4 = - 20
3) - 1 2/3 - (- 20) = 20 - 1 2/3 = 19 3/3 - 1 2/3 = 18 1/3